The Relationship of Serum 25-Hydroxyvitamin-D Level with Severity of Obstructive Sleep Apnea in Patients with Type 2 Diabetes Mellitus - Ma D; Zheng X; Dong L; Zheng C; Chen Y; Chen Z; Lin M; Li X; Li Z; Liu C (Diabetes, Metabolic Syndrome and Obesity, 2020)
Danyan Ma,1,* Xuanlin Zheng,2,* Lianqin Dong,3 Caiyu Zheng,4 Yun Chen,3 Zheng Chen,2 MingZhu Lin,2 Xuejun Li,5 Zhibin Li,6 Changqin Liu3,7 1School of Medicine, Xiamen University, Xiamen City, Fujian Province, People’s Republic of China; 2Department of Endocrinology and Diabetes, Xiamen Clinical Medical Center for Endocrine and Metabolic Diseases, Fujian Province Key Laboratory of Diabetes Translational Medicine, The First Affiliated Hospital of Xiamen University, Xiamen City, Fujian Province, People’s Republic of China; 3The School of Clinical Medicine, Fujian Medical University, Fuzhou, Fujian Province, People’s Republic of China; 4Fujian Medical University Xiamen Humanity Hospital, Xiamen City, Fujian Province, People’s Republic of China; 5Department of Endocrinology and Diabetes, Xiamen Clinical Medical Center for Endocrine and Metabolic Diseases, Fujian Province Key Laboratory of Diabetes Translational Medicine, Xiamen Diabetes Institute, The First Affiliated Hospital of Xiamen University, Xiamen City, Fujian Province, People’s Republic of China; 6Epidemiology Research Unit, The First Affiliated Hospital of Xiamen University, Xiamen City, Fujian Province, People’s Republic of China; 7Department of Endocrinology and Diabetes, Xiamen Clinical Medical Center for Endocrine and Metabolic Diseases, Fujian Province Key Laboratory of Diabetes Translational Medicine, The First Affiliated Hospital of Xiamen University, Xiamen City, Fujian Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Changqin LiuDepartment of Endocrinology and Diabetes, Xiamen Clinical Medical Center for Endocrine and Metabolic Diseases, Fujian Province Key Laboratory of Diabetes Translational Medicine, The First Affiliated Hospital of Xiamen University, Xiamen City, Fujian Province, People’s Republic of ChinaTel +86-592-2137610Fax +86-592-2137557Email liuchangqin@xmu.edu.cnZhibin LiEpidemiology Research Unit, The First Affiliated Hospital of Xiamen University, Xiamen City, Fujian Province, People’s Republic of ChinaTel +86-592-2137364Fax +86-592-2137557Email zhibinli33@hotmail.comObjective: To explore the association of serum vitamin-D levels with the severity of obstructive sleep apnea (OSA) in patients with type 2 diabetes mellitus (T2DM).Methods: A cross-sectional study of 136 patients with T2DM who underwent overnight polysomnography (PSG) tests and serum 25‐hydroxyvitamin‐D3 (25(OH)D3) level detections was conducted. Multivariable linear regression and logistic regression analyses were performed to determine the associations of serum 25(OH)D3 levels with apnea–hypopnea index (AHI) and obstructive sleep apnea (OSA).Results: The prevalence rates of OSA were 84.4% for male and 65.2% for female patients, respectively (p = 0.011). With increasing severities of OSA categories (none, mild, moderate and severe), patients were more likely to be male and obese, but there was no significant difference in serum 25(OH)D3 level ((mean ± standard deviation) 21.8 ± 8.8, 27.7 ± 14.6, 24.2 ± 9.8 and 26.8 ± 6.2 ng/mL, respectively, p=0.086). Serum 25(OH)D3 level was not significantly correlated with AHI (log-transformed), with the correlation coefficient of 0.133 (p=0.124). With adjustment for potential confounding factors, multivariable linear regression and logistic regression analyses showed that serum 25(OH)D3 level was not significantly associated with either AHI (log-transformed) or the risk of OSA, with the standardized regression coefficient (95% confidence interval (CI)) of 0.098 (− 0.004– 0.014, p=0.252) and the adjusted odds ratio (95% CI) of 1.055 (0.991– 1.124, p=0.095), respectively.Conclusion: Serum 25(OH)D3 level was not significantly associated with either AHI or the risk of OSA in patients with T2DM.Keywords: obstructive sleep apnea, polysomnography, 25-hydroxyvitamin-D3, apnea–hypopnea index, type 2 diabetes mellitus